(untitled) (Orfeu, 2023)
The article presents the result of a research with a qualitative approach on inclusive actions by music educators in the Projeto Guri/SP, considering music and musical learning from the perspective of inclusion (social and of People with Disabilities/Disorders) and comprehensive education (LECLERC; MOLL, 2012) by the belief in human potential: the “being more” (FREIRE, 2003), which reinforces the conviction that every human being is capable of learning and fully developing. It uses document analysis and focus groups as instruments and Vygotsky’s cultural-historical theory (2012) and Swanwick’s musical plurality (2003) as a theoretical source, having imagination as the source of the creative process (for students and educators), allied to importance of adopting meaningful educational actions and reflective practices in non-formal education contexts (TRILLA, 2008; GOHN, 2015; 2010). Finally, it presents reflections on the work of music educators and managers committed to a socially fair, inclusive and culturally significant education.